Analyzing Learning Obstacle with Didactical Design Research on Three Dimensional Distance Material - Dharma, Dian; Kamid, Kamid; Yantoro, Yantoro (Universitas Islam Negeri Raden Intan Lampung, 2021)
he purpose of this study was to analyze the barriers to learning three-dimensional distance material using Didactical Design Research (DDR). The subjects of this study were two groups of class 12. The instruments used in this study were pretest (initial test) and post test (final test) which consisted of a test of the respondent’s ability, interview sheets, and observation notes. The data obtained were analyzed using three DDR steps: (1) didactic situation analysis by recontextualizing, repersonalizing, and developing didactic designs which include PDA (Pedagogical Didactic Anticipation); (2) metapedadidactic analysis by applying PDA; and (3) retrospective analysis linking didactic and metapedadidactic situations. The results showed that the identified learning obstacles can be anticipated by using PDA. The application of the didactic learning design shows that this design can be an alternative to third-dimensional distance learning in grade 12 because it can minimize student learning barriers that have been identified previously.